2020
DOI: 10.3389/fpsyt.2020.00344
|View full text |Cite
|
Sign up to set email alerts
|

Possible Long-Term Effects of Childhood Maltreatment on Cognitive Function in Adult Women With Posttraumatic Stress Disorder

Abstract: Accumulated evidence shows that individuals with posttraumatic stress disorder (PTSD) have compromised cognitive function. PTSD is associated with childhood maltreatment, which also can negatively affect cognitive function. It is therefore possible that cognitive dysfunction in adult patients with PTSD can be due at least partly to childhood maltreatment, although little is documented on this issue. Here we aimed to examine the possible effect of childhood maltreatment on cognitive function in adult patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
0
11
0
2
Order By: Relevance
“…Second, as we only included female participants, it is unknown whether the present findings might be specific to women or common to both sexes. The main reason for the focus on female patients was that this study built on our previous studies of childhood maltreatment, cognitive function, memory bias, inflammation, and the BDNF Val66Met polymorphism in women with PTSD 61,[92][93][94] . In addition, it was necessary to consider potential sex differences in this study, given the evidence for differential psychobiological impacts of childhood maltreatment between sexes 95 and for sexually dimorphic effects of the BDNF Val66Met polymorphism 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, as we only included female participants, it is unknown whether the present findings might be specific to women or common to both sexes. The main reason for the focus on female patients was that this study built on our previous studies of childhood maltreatment, cognitive function, memory bias, inflammation, and the BDNF Val66Met polymorphism in women with PTSD 61,[92][93][94] . In addition, it was necessary to consider potential sex differences in this study, given the evidence for differential psychobiological impacts of childhood maltreatment between sexes 95 and for sexually dimorphic effects of the BDNF Val66Met polymorphism 49 .…”
Section: Discussionmentioning
confidence: 99%
“…As the RBANS is designed to be repeatable, administering this assessment on multiple occasions will yield valuable information about the examinee’s neuropsychological status across time points. Nakayama et al (2020) have found that among a sample of women who have developed PTSD due to interpersonal violence, performance on immediate memory, language, attention, and total RBANS scores were lower than those who did not experience such violence.…”
Section: Evaluation Proceduresmentioning
confidence: 98%
“…Therefore, it is possible that post-traumatic sequelae more complex than PTSD – i.e., cPTSD – may lead to nuanced psychotic symptoms, such as cognitive/excitative symptoms. Given that adults with PTSD following childhood maltreatment scored significantly higher on cognitive dysfunction than those without such experiences ( Nakayama et al, 2020 ), and also given that cPTSD is often associated with prolonged, repeated traumatic experiences during childhood, it is plausible that cPTSD may incur greater cognitive consequences than PTSD. Preliminary findings support this hypothesis, demonstrating that childhood trauma is linked to subjective and objective cognitive difficulties among people with psychosis, including working memory and attention ( Reinhard et al, 2010 ; Vargas et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%